Relationship Between The Amount Of Protein Intake And The Weight Gain Of Pregnant Women During Pregnancy With Low Birth Weight Babies - Widiasih, Esti; Nadila, Nadila; Tursinawati, Yanuarita (Ahmad Dahlan Medical Journal, 2025)
Protein intake is the main determinant in the survival, growth and development of the embryo while weight gain during pregnancy is needed to support the development and growth of the fetus in the womb. Birth weight is also related to the fulfillment of nutrition during pregnancy, where the fulfillment of maternal nutrition can be measured through its anthropometry, namely weight gain during pregnancy. This study aims to prove the relationship between the amount of protein intake and the weight gain of pregnant women during pregnancy with the baby's birth weight. This research method was analytic observational with a case control design. The research subjects were mothers who had babies with normal and low birth weight who met the inclusion and exclusion criteria. The sampling technique was purposive sampling. The research instrument was using the SQ-FFQ questionnaire about protein intake with interviews by nutritionist enumerators. Statistical test was using Chi-square correlation. A total of 32 research subjects, the majority aged 20-35 years (81.2%), moderated educational status (62.5%), low economic status (50%), parity was not at risked (84.4%), weight gain was appropriated ( 56.3%) and low protein intake (53.1%). The chi-square test obtained a p value of 0.013 and a p value of 0.021, which means that there was a relationship between the amount of protein intake and the weight gain of pregnant women during pregnancy with the birth weight of the baby.